PENGARUH JUMLAH ASET, JUMLAH SIMPANAN DAN JUMLAH ANGGOTA TERHADAP SISA HASIL USAHA (SHU) PADA KOPERASI SIMPAN PINJAM (KSP) SURU PUDI KOTING - Wejor, Angela Stefani; Herdi, Henrikus; Rangga, Yoseph Darius Purnama (Universitas Nusa Nipa Maumere, 2025)
This research aimed to analyze the influence of total assets, total savings, and the number of members on the Remaining Business Results of Suru Pudi Koting Credit Union in Sikka Regency. This research used a quantitative approach using secondary data from the credit unios's financial reports for the 2020-2024 period. The data analysis techniques used include the classical assumption tests, regression analysis, hypothesis testing, and the coefficient of determination. The results showed that total assets, total savings, and the number of members had no significant effect, either partially or simultaneously, on the Reamining Operating Results of Suru Pudi Koting Credit Unios.